LncRNA Expression Profiles in Systemic Lupus Erythematosus and Rheumatoid Arthritis: Emerging Biomarkers and Therapeutic Targets - Wu, Han; Chen, Shuxian; Li, Aifen; Shen, Kangyuan; Wang, Shuting; Wang, Sijie; Wu, Ping; Luo, Wenying; Pan, Qingjun (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) are two common multisystem autoimmune disorders that share many clinical manifestations, serological features, etc. The role of lncRNAs has been of particular interest in the pathogenesis of autoimmune diseases. Here, we aimed to summarize the roles of lncRNAs as emerging novel biomarkers and therapeutic targets in SLE and RA. We conducted a narrative review summarizing original articles on lncRNAs associated with SLE and RA, published until October 1, 2021. Based on the studies of lncRNA expression profiles in samples (including PBMCs, serum, and exosomes), it was noted that most of the current research is focused on investigating the regulatory mechanisms of these lncRNAs in SLE and RA. Several lncRNAs have been hypothesized to play important roles in SLE and RA. For SLE, lncRNAs such as GAS5, NEAT1, TUG1, linc0949, and linc0597 are dysregulated and may serve as emerging novel biomarkers and therapeutic targets. For RA, many validated lncRNAs, such as HOTAIR, GAS5, and lncRNA HIX003209, have been identified as promising novel biomarkers for the diagnosis and treatment. The shared lncRNAs, for example, GAS5, may participate in SLE pathogenesis through the mitogen-activated protein kinase pathway and can activate the AMP-activated protein kinase pathway in RA. Here, we summarize the data on key lncRNAs that may drive the pathogenesis of SLE and RA and could potentially serve as emerging novel biomarkers and therapeutic targets in the coming future.